Integracja i sieciowanie kobiet w zawodowej służbie wojskowej. Doświadczenia wybranych państw członkowskich NATO - Judzińska, Aneta (Studia Edukacyjne, 2025)
Integration among women in professional military service remains a relatively rare topic in the literature on the subject, despite its significant importance for the psychological well-being and professional functioning of female soldiers. The aim of this article is to identify and analyze selected positive practices used or implemented in NATO member states, aimed at supporting and developing integration among female soldiers. The article offers examples of institutional and grassroots solutions, with particular emphasis on networking initiatives, a possible source of inspiration for identifying adequate solutions in the Polish context.